STAFFING DAN FENOMENA RANGKAP JABATAN DI SEKOLAH ISLAM - Nurmalasari, Inten; Prayoga, Ari; Irawan, Irawan (Madrasa: Journal of Islamic Educational Management, 2019)
Some programs of Junior High School (SMP Muslimin 5 Kota bandung) were not implemented optimally because the position of teachers qualifications and competencies were not suitable for the mandate. In addition, double positions was unavoidable. This article aims to uncover the staffing process and the raising of double position phenomena in SMP Muslimini 5 Kota Bandung, West Java. The results showed that staffing had an impact on the raising of double positions. Double positions cannot be avoided because of the demands of fulfilling teaching hours, avoiding job vacancies and learning, inequality of competencies and potential teachers and the need for promotion and regeneration. Double or multiple positions have not optimized the potential SMP Muslimin 5 Bandung as an Islamic education institution (Islamic school). Positions related to the implementation of Islamic religious education have not attracted the interest of the teachers who wish to promote such as being the supervisor of the Madrasah Science Competition and Islamic religious extracurricular coaches.